2017
DOI: 10.3390/molecules22101718
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal 2-Hydroxyacyl-CoA Lyase Is Involved in Endogenous Biosynthesis of Heptadecanoic Acid

Abstract: Circulating heptadecanoic acid (C17:0) is reported to be a pathology risk/prognosis biomarker and a dietary biomarker. This pathology relationship has been shown to be reliably predictive even when independent of dietary contributions, suggesting that the endogenous biosynthesis of C17:0 is related to the pathological aetiology. Little is known about C17:0 biosynthesis, which tissues contribute to the circulating levels, and how C17:0 is related to pathology. Hacl1+/− mice were mated to obtain Hacl1−/− and Hac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…These data support that circulating OCFA levels can be effectively raised proportionally by the amount of dietary OCFAs ingested. Similar findings have been reported for C15:0 in humans; in contrast, C17:0 blood levels in humans do appear to be higher than expected given dietary C17:0, supporting endogenous production of C17:0 [6,[21][22].…”
Section: Plos Onesupporting
confidence: 84%
“…These data support that circulating OCFA levels can be effectively raised proportionally by the amount of dietary OCFAs ingested. Similar findings have been reported for C15:0 in humans; in contrast, C17:0 blood levels in humans do appear to be higher than expected given dietary C17:0, supporting endogenous production of C17:0 [6,[21][22].…”
Section: Plos Onesupporting
confidence: 84%
“…In the literature it is shown that C15:0 and C17:0 may originate from different sources; C15:0 comes directly from the diet, while C17:0 is also significantly endogenously biosynthesized [2,7]. The results presented here support a dietary origin for C15:0, since the in vivo C15:0 compositions decrease with an increase in dietary total-fat.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, there is convincing evidence showing that C17:0 does not directly relate to dietary intake. Instead, C17:0 endogenous biosynthesis has a significant influence on its circulating levels [2,7]. Furthermore, the literature suggests that C17:0 may have a significant pathophysiological relevance and could be subject to in vivo homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally after activation to its CoA-ester, pristanoyl-CoA undergoes three cycles of β-oxidation in peroxisomes prior to transport of end products to mitochondria for complete oxidation (36) . Both propionyl CoA and pristanal produced in peroxisomes by phytanoyl-CoA 2-hydroxy lyase activity are important precursors for biosynthesis of OCFA (39) (Fig. 2).…”
Section: Peroxisomes In Fatty Acid α-And β-Oxidationmentioning
confidence: 99%